Effect of conservation agriculture on soil fertility in maize (Zea mays)-based systems - CHAUDHARY, AMRESH; MEENA, MAHESH C; DWIVEDI, B S; DATTA, S P; PARIHAR, C M; DEY, ABIR; SHARMA, V K (The Indian Journal of Agricultural Sciences, 2019)
A long-term field experiment on conservation agriculture (CA) was initiated in sandy loam soil of Indo-Gangetic plain in 2008 at Research Farm of ICAR-IARI, New Delhi with 3 tillage practices, i.e. permanent bed (PB), zero-tillage (ZT) and conventional tillage (CT) in main plots and four maize-based cropping systems, i.e. maize-wheat-mungbean (MWMb), maize-chickpea-sesbania (MCS), maize-mustard-mungbean (MMuMb), maize-maize-sesbania (MMS) in sub-plots, in a split- plot design with three replications to evaluate the long-term effects of CA practices on maize yield and soil fertility under maize-based cropping systems. The current study was undertaken in kharif maize 2015 after completion of seven years of experimentation. Soil fertility parameters like mineral nitrogen (N) (NO3 – and NH4 +), available phosphorus (P), potassium (K), sulphur (S) and micronutrients (Zn, Fe, Mn, Cu) were determined from 0–5, 5–15 and 15–30 cm of soil depths. The available macronutrients (N, P, K and S) and micronutrients (Zn, Fe, Mn, Cu) were higher under PB and ZT compared with CT. Among the cropping systems, MCS and MWMb performed equally in relation to nutrient availability. The grain yield of maize was significantly higher under PB (5.55 t/ha) and ZT (5.49 t/ha) as compared to CT (4.81 t/ha), whereas MCS and MWMb performed better in term of maize productivity as compared with MMuMb and MMS. Thus, the long-term study suggested that ZT and PB under diversified cropping systems such as MWMb and MCS could be the best agricultural practices for sustainable production as well as nutrient availability in maize-based cropping systems.